Challenges in Dealing with Supervised and Institutionalized Populations in a Disaster. Issue Volume 34:Issue s1(2019) (May 2019) - Mace, Sharon; Doyle, Connie
Abstract : Introduction: Those residing in supervised facilities including nursing homes, mental health facilities, group homes, and penal institutions for health, legal, or security reasons present unique challenges in a disaster. Methods: A review of the literature and after action reports on supervised and institutionalized populations in disasters. Results: Recommendations for supervised, institutionalized populations in a disaster include: (1.) preplanned agreements for specialized transportation if needed; (2.) reciprocal agreements between similar facilities (nursing home with another nursing home, prison with other prison, dialysis centers, etc.) for resource sharing; (3.) arrangements for sharing and emergency privileging of personnel in institutions that are not their primary workplace; (4.) just-in-time training for appropriate volunteers; and (5.) accommodations for family members if personnel are to be available during a disaster. Individuals in some institutions need a personalized disaster plan with pertinent data: next of kin with contact information, medical records, care providers and care plan to accompany a mobilized individual. Long-term care and housing may be needed if the institution is nonfunctional. Dealing with medical and behavioral issues is secondary to the disaster. Chronic issues must be considered as well. Discussion: Caring for specialized, institutional individuals is complex and difficult. Comprehensive pre-disaster planning can mitigate the effects of the disaster.